Biliary atresia in a preterm and extremely low birth weight infant: a case report and literature review - Yuki Kawano; Koichiro Yoshimaru; Yasuyuki Uchida; Keisuke Kajihara; Yukihiro Toriigahara; Takeshi Shirai; Yoshiaki Takahashi; Toshiharu Matsuura (Surgical Case Reports)
Abstract Background Biliary atresia in very low birth weight (VLBW) and extremely low birth weight (ELBW) infants is rarely reported, and the optimal timing of Kasai portoenterostomy (KPE) in these cases remains unclear. Case presentation We report a case of biliary atresia in a preterm female infant of 24 weeks of gestation who weighed 824 g. She underwent exploratory laparotomy and intraoperative cholangiography at 58 days of age (weight, 1336 g). Despite the diagnosis of biliary atresia with a type I cyst, we could only perform gallbladder drainage at that time due to the unstable intraoperative condition. While we waited for her body weight to increase, KPE was performed at 122 days of age (corrected age: 16 days), when the patient weighed 2296 g. Although she initially became jaundice-free, her liver function deteriorated due to cholangitis, and she developed decompensated cholestatic liver cirrhosis. Living donor liver transplantation was successfully performed at 117 days after KPE, and the postoperative course was uneventful. The timing of KPE is difficult to determine and a review of the relevant literature revealed that a poor prognosis in VLBW and ELBW infants with BA. Conclusions Early KPE and careful postoperative follow-up, including liver transplantation is important for the improvement of outcomes.